Analisis Faktor Yang Mempengaruhi Perilaku Pencegahan Penularan Pada Pasien Tuberkulosis Paru - Rachma, Widiyas Ulfia; Makhfudli, Makhfudli; Wahyuni, Sylvia Dwi (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:  The purpose of this study was to explain the factors that influence transmission prevention behavior in pulmonary tuberculosis patients and the types of behavior associated with themMethods:  This study was using Literature Review as design research. Researchers were using journals taken from SCOPUS, DOAJ, PUBMED, and SINTA. The reviewed journals were in English and Indonesian published around 2016 to 2020. After that, the researcher conducted a JBI critical appraisal on the journal reviewResults: Factors that influence transmission prevention behavior in pulmonary tuberculosis patients were including self-efficacy, knowledge, attitude, practices, family support, health education, perception, and behavior before the illness. Type of behavior TB prevention was including cough etiquette (86.2%), washing hands with soap (79.17%), opening windows at home (88%), patients routinely taking medication for 6 months (88%). Conclusion:  Knowledge and health education with brainstorming and booklets were the dominant factors in  Pulmonary Tuberculosis prevention behavior. The dominant type of  Pulmonary Tuberculosis transmission prevention was opening house window.